(untitled) (Annals of Medical Research, 2022)
Aim: To compare the effectiveness of computed tomography (CT) angiography (CTA), CT Perfusion (CTP) spot signs, and CTP parametric maps obtained from the examinations performed on a 16-slice CT for predicting acute intraparenchymal hematoma (AIPH) progression. Materials and Methods: Thirty-one patients who presented to the emergency department with acute neurological symptoms and were diagnosed with AIPH on initial head CT examination were included in this study. The patients were administered CTA and CTP within 3 hours of the diagnosis of AIPH and follow-up head CT 24 hours after the first diagnosis. Diagnostic performance of spot signs in CTA and CTP, abnormality presence in CTP parametric maps, and the relationship between them and hematoma progression were investigated. Results: Sensitivity, specificity, positive predictive, negative predictive and accuracy values in predicting hematoma progression were 85.7%, 95.8%, 95.8%, 85.7%, and 93.5% for CTA spot sign; 71.4%, 95.8%, 83.3%, 92% and 83.9% for CTP spot sign; 14.3%, 87.5%, 100%, 87.5% and 70.9% for all CTP parametric maps, respectively. CTP parametric maps could not be created due to motion artifacts in 19.4% of patients. Conclusion: The spot sign is a valuable finding that predicts hematoma progression on CTA and CTP examinations performed on a 16-slice CT device. On the other hand, perfusion maps obtained from CTPs are less effective in predicting hematoma progression. Motion artifacts can be seen with a significant frequency in AIPH cases and may prevent the formation of parametric perfusion maps. Limitations of CT equipment and methods should be considered when deciding on the correct method to predict the hematoma progression.